Nyai Walidah Tokoh Pendidikan Nasional dan Perjuangan dalam Pendirian Froebel Kindergarten Aisyiyah - Sifa Nur Aesti (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2024)
This research aims to find out the history of Nyai Walida's services as a female figure who fought for women's equality and early childhood education in the 20th century through the organization she founded (Aisyiyah) with KH Ahmad Dahlan. Therefore, the research method used is historical study. This research uses a literature study approach. The data collection technique uses library study techniques which are guided by heuristic understanding. The results of this research show that the existence of Nyai Walida has a strong contribution in providing the foundation for the values ​​of early childhood education in Froebel Kindergarten including independence, integrity, and Nyai Walida's ideas which have survived to this day. So that Nyai Walida became a national education figure.